1988
DOI: 10.1017/s0767399x0000225x
|View full text |Cite
|
Sign up to set email alerts
|

The thyrotropin-releasing hormone test in depressed and non-depressed psychiatric patients

Abstract: SummaryThe thyrotropin-releasing hormone (TRH) test was carried out in 231 depressed patients undergoing a dexamethasone suppression test (DST), and in 63 psychiatric control patients. The patients were classified according to DSM-III. Thyrotropin-secreting hormone (TSH) was determined in basal conditions, 20 and 60 min after the administration of 200 μg TRH. The Δ max TSH values (peak TSH response minus basal TSH) showed no significant difference between psychiatrie Controls and patients with major depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1989
1989
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…Deze significante discriminatie van beide depressieve toestandsbeelden berust ten dele op de ernst van de depressie: een melancholie is een ernstiger ziekte dan de andere depressieve groepen, terwijl ook een negatief verband tussen het TSH-antwoord en de ernst van de ziekte is vastgesteld (een negatieve correlatie met de Hamilton Depressie Score). 16 ' 17 ' 19 SPECIFICITEIT VAN DE TRH-TEST…”
Section: De Trh-test En Depressieunclassified
See 1 more Smart Citation
“…Deze significante discriminatie van beide depressieve toestandsbeelden berust ten dele op de ernst van de depressie: een melancholie is een ernstiger ziekte dan de andere depressieve groepen, terwijl ook een negatief verband tussen het TSH-antwoord en de ernst van de ziekte is vastgesteld (een negatieve correlatie met de Hamilton Depressie Score). 16 ' 17 ' 19 SPECIFICITEIT VAN DE TRH-TEST…”
Section: De Trh-test En Depressieunclassified
“…Dit wordt schematisch geillustreerd in figuur 1. Uit onze ervaring blijkt nochtans dat zelf bij gecombineerd gebruik van beide tests de sensitiviteit te laag is om echt klinisch bruikbaar te zijn 16.…”
unclassified
“…The test consists of TRH administration, and determination of peak and baseline (threshold) levels of blood TSH. Age, sex, metabolic and thyroid status, treatment, and depressive characteristics may influence test results (Extein et al, 1982;Loosen eta/, 1982;Baumgartcn et al, 1985;Maes et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The stimulating dose of TRH is difficult to determine. Authors have used from 200 (Kirkegaard et al, 1978;Maes et al, 1988); to 550 fig TRH, and Masturzo et al (1988) have demonstrated the influence of dose variation.…”
Section: Introductionmentioning
confidence: 99%